Rancang Bangun Sistem Kontrol Suplai Beban PLTS Menggunakan Pulse Width Modulation dan Real Time Clock - Andareas Pangkung; Shiti Qamariah; Sukma Abadi; Nur Intan Mayasari (Jurnal Teknik Mesin Sinergi, 2022)
The increasing need for energy makes people prefer to develop alternative energy. The sun is the main source of energy to the earth's surface. In sunny weather conditions, solar energy is about 1000 Watt/m2. The cheap source of solar energy causes many parties to use its energy, one of which is for street lamp lighting. The limited time of the sun to produce energy must be make solar energy is stored in batteries so that it can be used at night. However, the battery also has limitations in storing energy which results in less efficient use of PLTS. Therefore, it is necessary to adjust the loading using a controller that is able to regulate how much energy the battery must release according to the needs at that time so that there is no more wasted battery expenditure. With this controller, alternative energy will be used more efficiently. Making the tool begins by looking for some reference components that are capable of being the main material, then doing assembly and continuous testing of the tool to see if the controller runs as desired. It is hoped that this tool can be applied on roads and other places that require load supply regulation. The test results during the tool making process prove that the presence of a load supply regulator controller makes the battery more efficient to use